INCULCATING HINDU-BASED RELIGIOUS AND MORAL VALUES IN EARLY CHILDHOOD (A CASE STUDY OF PRATAMA WIDYALAYA DHARMA KUMARA) - I Wayan Rudiarta; I Wayan Lasmawan; Desak Putu Parmiti (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2026)
The development of religious and moral values in children is an important aspect in Early Childhood Education. Pratama Widyalaya Dharma Kumara, as the only Widyalaya in Mataram City, strives to organize education by emphasizing the cultivation of Hindu values. This study aims to comprehensively analyze how religious and moral values are internalized from an early age and how they contribute to the formation of children's character. This study uses a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation studies, then analyzed using the Miles, Huberman, and Saldaña model. The results of the study show that the cultivation of religious and moral values in Pratama Widyalaya Dharma Kumara is carried out through various activities, namely Tri Sandhya together, prayer before meals, learning activities, and going home, Purnama-Tilem worship together, and prayer at the temple (outing class). The development of religious and moral values in children is evident in behavioral changes, such as the habit of saying "Om Swastyastu", responding to instructions, paying closer attention to the teacher's directions, praying before activities, speaking more politely, and showing concern for the surrounding environment. This research emphasizes the importance of internalizing religious and moral values in Early Childhood Education and the need to strengthen their implementation in other Early Childhood Education institutions. However, because the study was limited to a single location and a small number of subjects, follow-up research with a broader scope is urgently needed to yield more comprehensive results.